Asymmetric doupoly competition with innovation spillover and input constraints - Chen, You-hua; Nie, Pu-yan; Wang, X. Henry (Journal of Business Economics and Management, 2015)
This paper subjects to examine how technology spillover affects input competition and how input constraints impact firm innovation by a two-stage game model and theoretic analysis. The results show that with low spillover, the high cost firm can capture more input than the low cost firm through cost-reducing innovation. Adding input increases firms’ innovation, but it cannot improve the disadvantaged firm's state under input constraint. Compared with non-cooperative innovation, cooperative innovation reduces innovation difference and firm size difference. The research implications are that disadvantage firms could take innovation spillover and capacity constraints as a competition strategy to obtain competition advantage and regulators should stimulate cooperative innovation to higher social welfare. The major value of this paper is that it combines capacity constraints and innovation investment originality.